Penerapan Model Project Based Learning dalam Meningkatkan Kemampuan Berpikir Kritis dan Kreativitas pada Mata Pelajaran Sanggul Malam Peserta Didik di SMKN 8 Surabaya (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study is intended as a means to measure students' abilities through a project-based learning approach. The chosen procedure is Classroom Action Research (CAR), which consists of two stages: planning, implementation, observation, and reflection, involving class XI students at SMKN 8 Surabaya. Data were collected through observation, interviews, and learning outcome tests. The results of the study indicate that the implementation of Project-Based Learning effectively enhances students' creativity, as evidenced by the increase in average scores and active participation in learning activities. Based on these findings, the strategy is recommended as an effective approach for classroom learning.